Pengukuran Geolistrik dan Intensitas Gas Radon pada Penentuan Daerah Potensial untuk Pemboran Air Tanah-Dalam Desa Lebeng Barat Pasongsongan, Sumenep, Jawa Timur - Sukadana, I Gde (BRIN Publishing, 2013)
Lebeng Barat village, Pasongsongan sub-district is a village which has insufficient of fresh water, particularly in dry season. This region has a fairly dense population and equitable distribution of the population, therefore a sufficient supply of clean water for consumption and other needs are required. The purpose of study is to find out the ground-water potential zone in determination of exploration drilling points to develop ground-water’s well production. The methods used in this study as follow: Geological/hydrogeological mapping, measurement of radon intensity and geo-electric sounding survey with Schlumberger’s configuration. Exposed rocks within work areas can be classified into 5 (five) rocks unit, namely claystone with intercalation of limestone unit, inter bedded of calcareous sandstone and limestone unit, mudstone unit and limestone-claystone unit. The potential rock’s layer as aquifer is a layer of calcareous sandstone which has characteristic of pale yellow to brown, medium-coarse grained, sufficient permeability rocks (in the section exposed at the surface) include the limestone unit. Rock aquifers that serve on the bottom are included in inter bedded of calcareous sandstone and limestone unit. Potential points recommended for drilling exploration / production are the point of LBR-29 with the thickness of the aquifer 1 (shallower) 33.86 m and aquifer 2 (deeper) 23.72 m.